The effect of text messaging on latent tuberculosis treatment adherence: a randomised controlled trial. Issue 2 (8th February 2018) - Johnston, James C.; van der Kop, Mia L.; Smillie, Kirsten; Ogilvie, Gina; Marra, Fawziah; Sadatsafavi, Mohsen; Romanowski, Kamila; Budd, Matthew A.; Hajek, Jan; Cook, Victoria; Lester, Richard T.
There is limited high-quality evidence available to inform the use of text messaging to improve latent tuberculosis infection (LTBI) treatment adherence. We performed a parallel, randomised controlled trial at two sites to assess the effect of a two-way short message service on LTBI adherence. We enrolled adults initiating LTBI therapy from June 2012 to September 2015 in British Columbia, Canada. Participants were randomised in a 1:1 ratio to standard LTBI treatment (control) or standard LTBI treatment plus two-way weekly text messaging (intervention). The primary outcome was treatment completion, defined as taking ≥80% prescribed doses within 12 months (isoniazid) or 6 months (rifampin) of enrolment. The trial was unblinded except for the data analyst. A total of 358 participants were assigned to the intervention (n=170) and control (n=188) arms. In intention-to-treat analysis, the proportion of participants completing LTBI therapy in the intervention and control arms was 79.4% and 81.9%, respectively (RR 0.97, 95% CI 0.88–1.07; p=0.550). Results were similar for pre-specified secondary end-points, including time-to-completion of LTBI therapy, completion of >90% of prescribed LTBI doses and health-related quality of life. Weekly two-way text messaging did not improve LTBI completion rates compared to standard LTBI care; however, completion rates were high in both treatment arms. Weekly two-way text messaging did not improve latent tuberculosis treatment completion in a high-resource setting http://ow.ly/9gLA30hzSlE